Microsomal prostaglandin E synthase‐1 is involved in the metabolic and cardiovascular alterations associated with obesity - Ballesteros‐Martínez, Constanza; Rodrigues‐Díez, Raquel; Beltrán, Luis M.; Moreno‐Carriles, Rosa; Martínez‐Martínez, Ernesto; González‐Amor, María; Martínez‐González, Jose; Rodríguez, Cristina; Cachofeiro, Victoria; Salaices, Mercedes; Briones, Ana M. (British journal of pharmacology, 2022)
Background and Purpose Microsomal prostaglandin E synthase‐1 (mPGES‐1) is an inducible isomerase responsible for prostaglandin E2 production in inflammatory conditions. We evaluated the role of mPGES‐1 in the development and the metabolic and cardiovascular alterations of obesity. Experimental Approach mPGES‐1+/+ and mPGES‐1−/− mice were fed with normal or high fat diet (HFD, 60% fat). The glycaemic and lipid profile was evaluated by glucose and insulin tolerance tests and colorimetric assays. Vascular function, structure and mechanics were assessed by myography. Histological studies, q‐RT‐PCR, and western blot analyses were performed in adipose tissue depots and cardiovascular tissues. Gene expression in abdominal fat and perivascular adipose tissue (PVAT) from patients was correlated with vascular damage. Key Results Male mPGES‐1−/− mice fed with HFD were protected against body weight gain and showed reduced adiposity, better glucose tolerance and insulin sensitivity, lipid levels and less white adipose tissue and PVAT inflammation and fibrosis, compared with mPGES‐1+/+ mice. mPGES‐1 knockdown prevented cardiomyocyte hypertrophy, cardiac fibrosis, endothelial dysfunction, aortic insulin resistance, and vascular inflammation and remodelling, induced by HFD. Obesity‐induced weight gain and endothelial dysfunction of resistance arteries were ameliorated in female mPGES‐1−/− mice. In humans, we found a positive correlation between mPGES‐1 expression in abdominal fat and vascular remodelling, vessel stiffness, and systolic blood pressure. In human PVAT, there was a positive correlation between mPGES‐1 expression and inflammatory markers. Conclusions and Implications mPGES‐1 inhibition might be a novel therapeutic approach to the management of obesity and the associated cardiovascular and metabolic alterations.